Thermal hazard investigation of a pharmaceutical intermediate. Issue 2 (11th August 2017) - Zhao, Ralph; Muzzio, Dan; Vickery, Tom; Fisher, Elizabeth; Artino, Laura; Yin, Jay; Hinksmon, Joe; Fine, Adam
Abstract : During the process development of a pharmaceutical advanced intermediate, new chemistry using an aqueous workup resulted in the discovery of a new hydrated crystal form of this intermediate. This hydrated crystal form showed thermal instability at a relatively low temperature compared to the original anhydrous form. Thermal stability and associated process safety hazards were investigated in order to ensure process safety and transportation safety of this intermediate. © 2017 American Institute of Chemical Engineers Process Saf Prog 37: 263–267, 2018